Development of a Game-Based Learning Model to Improve Mathematical Problem-Solving Abilities in Class XI students at Pratidina Vocational School Makassar (Lembaga Pengembangan Kinerja Dosen, 2023)
This research focuses on developing a game-based learning model to improve students' mathematical problem-solving abilities of class XI students at SMK Pratidina Makassar. This model was designed to make the learning process more interesting and interactive while increasing students' understanding of mathematical concepts. Through a game approach, students are invited to think critically and analytically in solving mathematical problems, so that their problem-solving abilities can develop. The research results show that this game-based learning model is effective in improving students' mathematical problem-solving abilities. Apart from that, this model also succeeds in creating a more enjoyable learning atmosphere and students' learning motivation is higher. Therefore, this research recommends implementing a game-based learning model in teaching mathematics.